Optimizing the Implementation of Part-Time Government Employees with Work Agreements (PPPK) in Supporting Bureaucratic Reform in East Aceh Regency - Fakhri, Yanwar; Yusran Gea, Ali; Br. Sembiring, Tamaulina (International Conference Epicentrum of Economic Global Framework, 2026)
The Part-Time Government Employees with Employment Agreements (PPPK Part-Time) policy is an integral component of Indonesia’s civil service reform aimed at restructuring non-civil servant employees while maintaining the continuity of public service delivery. East Aceh Regency is among the regions with a significant number of Part-Time PPPK employees, totaling 5,077 personnel distributed across 61 regional government agencies. This condition requires the local government to establish an effective policy implementation framework to support bureaucratic reform. This study aims to analyze the implementation of the Part-Time PPPK policy in East Aceh Regency and formulate strategies for its optimization. The research employed an empirical juridical method using statutory and conceptual approaches supported by secondary data and interview findings. The results indicate that the implementation of the Part-Time PPPK policy has contributed to maintaining public service delivery, particularly in the education, health, and technical service sectors. However, the large number of Part-Time PPPK employees necessitates a more adaptive governance model through organization-based human resource management, performance evaluation focused on public service outcomes, continuous capacity development, and periodic policy evaluation. Optimizing the implementation of this policy is expected to strengthen bureaucratic reform while improving the quality of public services in East Aceh Regency.